EFFECT OF BAGASSE PORTION IN DIET ON BODY COMPOSITION OF GOAT - Baiti, I.Z.; Nuswantara, L.K.; Pangestu, E.; Wahyono, F.; Achmadi, J. (Diponegoro University, 2013)
The study was aimed to predict body composition of local goats fed bagasse based total mixedration (TMR). Fifteen male local goats (18 months old with average body weight of 18 kg ) were used inthis study. Goats were divided randomly into 3 groups, and were fed TMR’s those contained 15, 25, and35% of sugarcane bagasse, respectively. All experimental diets were designed to be isoenergy andisoprotein. After 12 weeks of adaptation to experimental diets and environment, each group wassubjected to feed digestibility trial, body composition, and experiment of feeding effect on serumglucose. The data were analyzed using one way analyses of variance. The results showed that the bodycomposition and serum glucose concentration were not significantly different (P>0.05) amongtreatments. The bagasse portion in the TMR upto 25% lowered daily feed consumption and body weightgain (P<0.05). It was concluded that the use of sugarcane bagasse up to 35% in the TMR did not affectbody composition of goats.